Laparoscopic Management of Abdominal Pregnancy Replaced in the Vesicouterine Pouch and Sacrouterine Ligament - Cihan Kaya; Murat Ekin (Medical Network, 2017)
AAbdominal pregnancies are rare and life threatening conditions with increased maternal mortality rate. A 37-year old woman admitted with acute abdominal pain. She had a history of dilatation and curettage due to anembryonic pregnancy five days ago. A pelvic X Ray confirmed an abdominally located IUCD. Her serum β-human chorionic gonadotropin level was 5531 mIU/ml.  A laparoscopy was performed and there was a round hemorrhagic mass in the vesicouterine pouch in exploration. The trophoblastic tissue was removed from the vesicouterine pouch and left sacrouterine ligament. The histopathology report revealed chorionic villi both of the excised specimens. The abdominal cavity should be explored carefully in suspicion of abdominal pregnancy and laparoscopic management is a feasible approach for this cases.